Effect Of Supplementation Of Organic Acids On Laying Performance, Body Fatness And Egg Quality Of Hens (Bangladesh Journal of Animal Science, 2012)
The study was conducted to determine the effect of organic acids supplementation on body weight changes, feed intake, feed efficiency, egg production, egg weight and egg quality in laying hens at age between 67 and 74 weeks. A total of 48 Shaver 579 laying hens of 67 weeks age were allotted into 4 groups, each containing 12 hens. The hens were fed basal diet (17% CP and 2800 kcal ME/kg diet) supplemented with 0 (T1), 260 (T2), 520 (T3) and 780 ppm (T4) of organic acid mixture (fumaric acid and salt of butyric, propionic and lactic acids). The results revealed no effect of organic acids supplementation on body weight change and feed intake but improvement of egg production and feed conversion were observed. Organic acids supplementation significantly increased egg production by about 2.26, 8.0 and 9.84% on 260, 520 and 780 ppm respectively when compared with the untreated group (P